Mating Strategies of Female Cetaceans - Orbach, Dara Nicole (2016)
This dissertation provides broad insights on aspects of sexual selection in cetaceans (whales, dolphins, and porpoises) and addresses the gap of knowledge regarding female mating strategies. A comparative approach is applied to investigate the coevolution of mating strategies between the sexes and between anatomy and behavior, using dusky dolphins (Lagenorhynchus obscurus) as a model species. There are several key outcomes: (1) A heuristic framework is developed for the coevolution of mating strategies, in which males have low monopolization potentials of females, females evolved evasive behavioral maneuvers, males evolved large relative testes sizes, and females evolved convoluted vaginas. (2) Female mating behaviors are assessed in the context of exploitative scramble competition. Female dusky dolphins display evasive behavioral maneuvers during mating chases and discriminate among male behaviors. (3) A standardized measurement protocol is developed for female reproductive tracts and the microstructure of the unusual vaginal folds found in cetaceans is explored. The vaginal morphology of common bottlenose dolphins (Tursiops truncatus) is conserved across sexual maturity and reproductive states and consists of one caudally-oriented vaginal fold. Vaginal fold tissue is comprised of smooth (autonomic origin), not skeletal muscle (somatic origin). (4) Issues of scaling are examined while controlling for phylogenetic relatedness across 19 species. Vaginal lengths and vaginal fold lengths are correlated with body length but not each other, setting the stage to test functional hypotheses. (5) Reproductive anatomy (post-copulatory mechanism) and mating behavioral effort (pre-copulatory mechanism) are explored across dusky dolphins, bottlenose dolphins, and harbor porpoises (Phocoena phocoena). A pattern appears between vaginal complexity and testes size. However, female pre-copulatory traits (behavioral repertoire size and intensity) do not match the trends predicted based on post-copulatory traits. Female dusky ...